Cover Image, Volume 25, Issue 4. (18th August 2018) - Egerer, Stefanie; Fiebig, Uwe; Kessler, Barbara; Zakhartchenko, Valeri; Kurome, Mayuko; Reichart, Bruno; Kupatt, Christian; Klymiuk, Nikolai; Wolf, Eckhard; Denner, Joachim; Bähr, Andrea
Abstract : The cover image, by Egerer et al., is based on the Original Article Early weaning completely eliminates porcine cytomegalovirus from a newly established pig donor facility for xenotransplantation . DOI:10.1111/xen.12449